Anti-cancer on carrageenan from red algae: Anti-kanker pada carrageenan dari alga merah - Ema Yusuf; Dian Rafika Sari D; Melinda Herman; Meuthia Narissa Azzahra; Surianti Alimin; Irene Edith Rieuwpassa (Makassar Dental Journal, 2023)
Cancers are serious diseases with various etiologies mainly due to unhealthy dietary habits and lifestyles. However, almost all drugs used for anti-cancer therapy are usually toxic and generally affect normal healthy cells, hence the search for new com-pounds that are effective, non-toxic and natural. In particular, algae contain many valuable components with great anti-cancer potential. Carrageenan is a general term describing a group of sulphated polysaccharides in red algae that present a major com-ponent of the cell wall and interstitial space functioning as a forming compound and providing intercellular adhesion and inter-cellular signalling. Carrageenan isolated from red algae has been the object of drug discovery over the past few decades as it exhibits anti-cancer capabilities.